The The Influence of Corporate Governance Perception Index, Profitability Ratio and Firm Size to Company Value (CGPI And Listed Companies On The IDX) - Eva Safina Rose; Siti Arbainah; Suko Raharjo; Ardian Widiarto (Yayasan Ilomata, 2021)
This research is based on the problem of what factors can affect the value of company in the form of book value of shares (PBV) in companies that are ranked CGPI and listed on the IDX 2014-2018. CGPI itself is a Corporate Governance index given by the IICG institution to participating companies in accordance with the results of research on corporate governance mechanisms. This study aims to analyze the effect of the Corporate Governance Perception Index, Profitability Ratios, and Company Size on Firm Value in companies that are ranked CGPI and listed on the IDX during the 2014-2018 period with a sample of 11 companies using purposive sampling technique. The results of Multiple Linear Regression Statistical Analysis show that (1) The effect of CGPI on Book Value of Shares (PBV) is positive and significant (2) The effect of ROA on Book Value of Shares (PBV) does not have a positive and significant effect (3) Effect of ROE on Firm Value (PBV) is positive and significant (4) The influence of Company Size on Company Value (PBV) does not have a positive and significant effect (5) CGPI, Return On Assets, Return On Equity, and Company Size simultaneously have an influence on Firm Value.